(untitled) (Journal of Bangladesh Academy of Sciences, 2014)
In this paper, the authors introduced two notions of fuzzy pairwise-T0 bitopological spaces and compared them with other such concepts. The authors also studied some other properties of these spaces. DOI: http://dx.doi.org/10.3329/jbas.v38i2.21345 Journal of Bangladesh Academy of Sciences, Vol. 38, No. 2, 209-217, 2014